O efeito das características das empresas na qualidade da informação contábil após a adoção das IFRS - Barros, Pedro Paulo Furbino Bretas (2019)
The International Financial Reporting Standards (IFRS) adoption has changed the way to recognize, measure and disclose accounting results. Studies on the impact of adopting such standards on the accounting quality are conflicting. This paper assumes the effect of IFRS is not equal for all companies, depending on the incentives existing to manage accounting results, which could explain the ambiguity in the literature. The paper aims to assess the effect from IFRS adoption on companies’ characteristics related to incentives to manage results. Book-tax difference (BTD) and discretionary accruals were used as earnings management proxies. Indebtedness, profitability and monitoring were considered variables related to earnings management incentive. The analysis covers the period between 2005 and 2014. Statistical regressions were performed with pooled data and differences of means between before and after the IFRS adoption. The results do not indicate an increase in the earnings management with the adoption of IFRS. In fact, the results indicate the opposite, being compatible with a negative effect of IFRS on the accounting result in the period, due to the recognition of losses without tax effect.